Studies on Homalomeneae (Araceae) of Borneo XX: Homalomena lambirensis sp. nov. from Sarawak with well-recorded pollination biology - Wong, Sin Yeng; Boyce, P.C (Blackwell Publishing Ltd., 2017)
Homalomena lambirensis S. Y. Wong & P. C. Boyce is described and illustrated as a new species of the Homalomena Hanneae complex [Cyrtocladon clade] from Lambir Hills National Park, northeast Sarawak, Malaysian Borneo to where it is endemic. Comparison with the described Bornean species of the Hanneae complex is made and an identification key to species is provided. Homalomena lambirensis has previously been the subject of detailed pollination biology studies under the erroneous identity Homalomena propinqua Schott (= H. rostrata Griff.). Recognition of H. lambirensis takes to 10 the total of described species for the Hanneae complex. © 2017 The Authors